Rethinking Matn Criticism in Hadith Studies: Insights from Mustafa Al-Siba‘i - Lutfianto, Mohammad (International Conference on Islamic Studies, 2024)
Hadith criticism is one of the important disciplines in Islamic studies that aims to assess the validity of the narration, both in terms of sanad and matan. One of the figures who pays serious attention to this is Must}afa> al-Siba>i>. This article discusses Must}afa> al-Siba>i>'s thoughts in the field of hadith matan criticism, by highlighting two main focuses: first, al-Siba>i>'s view of hadith as the main source of Islamic teachings and second, the approach and method of matan criticism that he offers. This article uses a descriptive qualitative method with a literature study approach to al-Siba>i>'s works and related literature. The results of this study are first; Must}afa> al-Siba>`i> said and believed that the purity of hadith was maintained during the time of the Prophet Muhammad SAW., this can be ascertained that there was never any forgery of hadith during the life of the Prophet Muhammad SAW. And hadith as the main source of Islamic teachings that has authority equal to the Qur'an, as well as the importance of preserving and validating hadith narrations. Second; According to Mustafa> al-Siba>`i> criticism of hadith is not something that should be avoided, but rather it should be criticized, but in criticizing hadith it must have a good intention or purpose to maintain or preserve the authenticity of the sunnah. Here he chooses to maintain a sunnah by following the path that has been etched by previous scholars